PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI ETOS KERJA PADA PT. NJEDUK DIGITAL MANDIRI - Dewi, Vina Fajar (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This research aims to determine the influence of the work environment and compensation on employee performance through work ethic at PT. Njeduk Digital Mandiri. The research used quantitative methods with saturated sampling techniques with a sample size of 32 respondents. The data analysis technique uses path analysis techniques to determine the direct and indirect influence of each research variable. The results of the research show that the work environment has a positive and significant effect on work ethic, the work environment has a positive and significant effect on employee performance, compensation has a positive and significant effect on work ethic, compensation has a positive and significant effect on employee performance, work ethic has a positive and significant effect on performance employees, work environment and compensation have a positive and significant effect on employee performance through work ethic. However, work ethic as an intervening variable is not able to strengthen the influence of the work environment and compensation on employee performance, because the relative contribution value of the direct path coefficient (direct effect) is greater than the relative contribution value of the indirect path coefficient (indirect effect).